Qualitative inquiry & research design : choosing among five approaches - Creswell, John W. (SAGE, 2018)
This book explores the philosophical underpinnings, history, and key elements of five qualitative inquiry approaches: narrative research, phenomenology, grounded theory, ethnography, and case study. The authors compare the approaches and relate research designs to each of the traditions of inquiry in a highly accessible manner. Featuring new content, articles, pedagogy, references, and expanded coverage of ethics throughout, the book is an introduction to the theories, strategies, and practices of qualitative inquiry.